Pemanfaatan Teknologi dalam Komunikasi Interpersonal oleh Santri Rantau dengan Orang Tua pada Tahun Ajaran 2023/2024: Studi Kasus di Pesantren Daar El-Qolam 3 Kampus Dza’izza, Jayanti, Kabupaten Tangerang - Nurdiyansyah, Shehan Dhepi; Sukanda, Ukon Furkon; Yoman, Mad (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This study aims to analyze the use of technology in interpersonal communication by students of Pesantren Daar El-Qolam 3 Kampus Dza'izza, Jayanti, Tangerang Regency. Interpersonal communication is a form of direct interaction between individuals, which involves the exchange of information face to face. Through this communication, individuals can influence each other, share feelings, and build relationships. This process is important for understanding other people's perspectives and creating closeness in social relations. Interpersonal communication does not only occur in the form of conversation, but also involves direct physical interaction (face to face). This study uses a qualitative descriptive approach with a case study method. The data used through interviews, observations, and documentation to caregivers of out-of-town students, out-of-town students and parents of out-of-town students. This study uses the Computer Mediated Communication (CMC) theory proposed by John December 1997. The results of this study indicate that the use of WhatsApp media technology with video call features is very helpful for long-distance interpersonal communication between students and their parents and the constraints of this study are technical problems or limitations of the technology they have, unstable or slow internet connections can affect long-distance communication, and time and time zone gaps, if communicating long distance there is usually a time zone gap with a different person.